PENERAPAN MODEL PEMBELAJARAN ALBICI (ACTIVE LEARNING BASED INTERACTIVE CONCEPTUAL INSTRUCTION) BERBANTUAN SIMULASI KOMPUTER UNTUK MENGUBAH MODEL MENTAL SISWA PADA MATERI FLUIDA DINAMIS - Fanny Herliyana Dewi, - (2019)
Mental models are interesting and important things to learn. Through a mental model a teacher can obtain information on students' thinking abilities and knowledge structures possessed by students that can be used as information to understand and accommodate student learning difficulties. The learning process is a mental model structuring process, so this study aims to obtain information about the influence of the ALBICI learning model assisted by computer simulations in changing students' mental models in dynamic fluid material. This research uses the embedded mix method research method with one group pre-test post-test design research, using the Fluid Dynamic-Four Tier Diagnostic Test instrument to obtain an overview of students' mental models and the samples studied are students of class XI MIPA 4 in Senior High Schools 6 Bandung. Mental models are analyzed through coding techniques calcified into scientific, syntets-A, syntetic-B, syntetic-C, syntetic-D, initial and uncode. The results of the study indicate that there is a change in the mental model in the direction expected after learning. So it can be concluded that the ALBICI learning model assisted by computer simulation can change the mental model of students.